Efektivitas Pelatihan Manajemen Stres Daring untuk Ibu dengan Anak yang Memiliki Gangguan Pemusatan Perhatian dan Hiperaktivitas (GPPH) - Adhissa Qonita; Fitri Lestari Issom; Iriani Indri Hapsari (Psychosophia: Journal of Psychology, Religion, and Humanity, 2022)
Many treatments for children with ADHD have been carried out, but on the other hand parents who interact directly with them have not been given much specific intervention. Parents with ADHD children are basically prone to experiencing stress in parenting, especially mothers. Interventions need to be carried out to help mothers not feel like they failed in parenting and to prevent the stress effect for the development of their ADHD children. This research was conducted to provide stress management training to reduce the level of parenting stress experienced by mothers with children who have a diagnosis of ADHD. This research is in the form of an experiment by comparing the level of stress experienced by mothers with GPPH children before and after being given training. Training is given over three days for approximately nine hours. Respondents in this study were 10 mothers with ADHD children who had moderate and severe levels of parenting stress based on a parenting stress measurement tool (Daulay & Hadjam, 2020). The results of the dependent t-test in this study were 0.000 <0.05. The results showed that there were differences in parenting stress levels before and after being given stress management training. Therefore stress management training is considered to be able to reduce the level of parenting stress experienced by mothers with ADHD children.